2002
DOI: 10.1126/science.1078721
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Shell Molecules That Ionize More Readily Than Cesium

Abstract: We report a class of molecules with extremely low ionization enthalpies, one member of which has been determined to have a gas-phase ionization energy (onset, 3.51 electron volts) lower than that of the cesium atom (which has the lowest gas-phase ionization energy of the elements) or of any other known closed-shell molecule or neutral transient species reported. The molecules are dimetal complexes with the general formula M2(hpp)4 (where M is Cr, Mo, or W, and hpp is the anion of 1,3,4,6,7,8-hexahydro-2H-pyrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 21 publications
6
105
0
1
Order By: Relevance
“…The employment of bicyclicg uanidinate HPP À (1,3,4,6,7,8hexahydro-2H-pyrimido[1,2-a]pyrimidinate) to prepared inuclear complexes ([M 2 (HPP) 4 ], M= Cr,M o, and W) was pioneered by Cottone tal. [129,130] The HPP À ligand wasa lso utilized to prepare the dicopper(I) complex [Cu(m-k 2 -HPP)] 2 (12)a nd the Xray-determined separation between two Cu atoms in 12 was 2.453(1) ,s lightly shorter than that in the bis-amidinate 10. [78] Consistent with the amidinate-supported dicopper complexes, the short Cu I -Cu I distance in 12 likely resulted from both strong Cu-N interactions and short N-N bite distances (ca.…”
Section: Nitrogen Donor-supported Dicopper(i) Complexesmentioning
confidence: 70%
“…The employment of bicyclicg uanidinate HPP À (1,3,4,6,7,8hexahydro-2H-pyrimido[1,2-a]pyrimidinate) to prepared inuclear complexes ([M 2 (HPP) 4 ], M= Cr,M o, and W) was pioneered by Cottone tal. [129,130] The HPP À ligand wasa lso utilized to prepare the dicopper(I) complex [Cu(m-k 2 -HPP)] 2 (12)a nd the Xray-determined separation between two Cu atoms in 12 was 2.453(1) ,s lightly shorter than that in the bis-amidinate 10. [78] Consistent with the amidinate-supported dicopper complexes, the short Cu I -Cu I distance in 12 likely resulted from both strong Cu-N interactions and short N-N bite distances (ca.…”
Section: Nitrogen Donor-supported Dicopper(i) Complexesmentioning
confidence: 70%
“…and NDP9 (Novaled, Dresden, Germany). The materials used as n‐dopants are acridine orange base (AOB; Sigma Aldrich, Steinheim, Germany) and tetrakis(1,3,4,6,7,8‐hexahydro‐2H‐pyrimido[1,2‐a]pyrimidinato)ditungsten (II) (W 2 (hpp) 4 ; see ref 67, 68…”
Section: Methodsmentioning
confidence: 99%
“…46 Here, hpp is the anion of 1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidine, and each molecule consists of 90 atoms. It has been found that the orbital relaxation has significant effects on the Fukui func- tions of the three molecules.…”
Section: Resultsmentioning
confidence: 99%
“…47 We first optimize the molecular structures with the B3LYP method, and the final structures agree well with the literature reports. 46,47 We then calculate the related energetic properties by using the HF method, and the results are shown in Table I. Apparently, the HF method systematically underestimates the vertical Is as compared to the experimental values, because of the lack of electron correlations.…”
Section: Resultsmentioning
confidence: 99%